Sprogteknologiske ordbaser for de nordiske sprog – rapport fra et forskningsnetværk - Pedersen, Bolette; Fjeld, Ruth V.; Gronostaj, Maria Toporowska (Nordiske Studier i Leksikografi, 2003)
This paper deals with a Nordic research network, SPINN, concerned with the harmonisation of Nordic, semantic computational lexica. Plans for extension of the lexica are described and some problems in adapting the Danish lexicon into a Norwegian version are accounted for. The main equivalence problems are caused by semantic changes which are taking place in modern Norwegian. These are changes with concequences for both internal and external lemma selection and especially the argument structure. Finally, a possibility to establish a multilingual network for Danish, Norwegian and Swedish is considered. The languages in the network will be interlinked by means of English, as described in The New Oxford Dictionary of English (NODE). Attention is also paid to some polysemy-oriented procedures supporting the interlingual linking.